Phosphate coating agent composition

KR103031189B1Active Publication Date: 2026-10-13(주)대주산업
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020260116965
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-13
Estimated Expiration
2046-06-26
Patent Text Reader

Abstract

The phosphate coating treatment agent composition according to the present invention is applied to fastening parts for building structures, etc., and comprises, based on 100 parts by weight of the total composition, 25 to 35 parts by weight of phosphoric acid, 23 to 33 parts by weight of zinc oxide, 18 to 28 parts by weight of nitric acid, 2 to 8 parts by weight of hydrated citric acid, 2 to 8 parts by weight of calcium carbonate, 2 to 8 parts by weight of nickel nitrate, 1 to 6 parts by weight of metallic manganese, and 0.5 to 3 parts by weight of copper sulfate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a phosphate coating agent composition for forming a protective film on a metal surface, and more specifically, to a phosphate coating agent composition capable of simultaneously providing a high level of precise dimensional control and excellent long-term corrosion resistance by minimizing thickness variations that occur during film formation. Background Technology

[0002] In this invention, background technology is provided, and this does not necessarily mean known technology.

[0003] In general, phosphate-based chemical conversion coating surface treatment methods are widely used to prevent corrosion of metal materials, including steel, and to maximize surface durability.

[0004] In particular, fastening components such as high-strength bolts, nuts, and washers for large construction structures like bridges, plants, and high-rise buildings, which require high tensile strength and high quality, require strong anti-corrosion performance due to their exposure to the external environment.

[0005] However, conventional phosphate coating agents used in the existing market had a fatal disadvantage in that the thickness varied significantly, ranging from 1 to 40 µm when forming a film.

[0006] For example, if significant variations in coating thickness cause parts to become excessively thick, workability issues arise where screw threads do not align, making assembly impossible. Conversely, if the coating forms too thinly, persistent quality instability issues occur, as the parts rust easily (red rust) when exposed to external environmental factors such as snow, rain, moisture, and salt, threatening the safety of the structure.

[0007] Therefore, there is an urgent need to develop a new phosphate coating agent composition that exhibits excellent corrosion resistance even in harsh corrosive environments while precisely controlling the final film thickness to stabilize thickness variations. Prior art literature

[0008] Korean Registered Patent Publication No. 10-1359967. The problem to be solved

[0009] The present invention aims to provide a phosphate coating agent composition that can prevent assembly defects of fastening parts and simultaneously provide excellent long-term corrosion resistance by precisely controlling and maintaining the final coating thickness within the range of 3 to 5 μm. means of solving the problem

[0010] A general summary of the invention is provided herein, and this should not be understood as limiting the scope of the invention.

[0011] To solve the above-mentioned problem, a phosphate coating treatment agent composition according to any one aspect of the present invention may comprise, with respect to 100 parts by weight of the phosphate coating treatment agent composition, 25 to 35 parts by weight of phosphoric acid, 23 to 33 parts by weight of zinc oxide, 18 to 28 parts by weight of nitric acid, 2 to 8 parts by weight of hydrated citric acid, 2 to 8 parts by weight of calcium carbonate, 2 to 8 parts by weight of nickel nitrate, 1 to 6 parts by weight of metallic manganese, and 0.5 to 3 parts by weight of copper sulfate.

[0012] In a phosphate coating treatment agent composition according to one aspect of the present invention, the phosphate coating treatment agent composition can be diluted by a solvent when used to form a phosphate coating with a thickness of 3 to 5 μm on a metal surface.

[0013] In a phosphate coating treatment agent composition according to one aspect of the present invention, the solvent may be diluted in a ratio of 1 to 9 parts by weight per 1 part by weight of the phosphate coating treatment agent composition.

[0014] In a phosphate coating treatment agent composition according to one aspect of the present invention, the solvent may include one or more of purified water, deionized water (DI water), or distilled water.

[0015] In a phosphate coating treatment agent composition according to one aspect of the present invention, the composition may be included in the ratio of 30 parts by weight of phosphoric acid, 28 parts by weight of zinc oxide, 23 parts by weight of nitric acid, 5 parts by weight of hydrated citric acid, 5 parts by weight of calcium carbonate, 5 parts by weight of nickel nitrate, 3 parts by weight of metallic manganese, and 1 part by weight of copper sulfate. Effects of the invention

[0016] According to the present invention, since the final film thickness can be ultra-precisely controlled and maintained within the range of 3 to 5 μm, it is possible to provide the effect of completely resolving dimensional errors between fastening parts such as construction bolts, nuts, and washers and minimizing the screw thread assembly defect rate.

[0017] In particular, when forming an ultra-precision thin film in the range of 3 to 5 μm, the friction characteristics between screw threads are uniformly controlled, thereby extremely stabilizing the clamping force and torque coefficient (K value), which are key quality indicators of high-strength construction bolts, and significantly improving the long-term fastening reliability of structures.

[0018] According to the present invention, since the phosphate film layer forms a dense structure that seals the metal surface without gaps, it is possible to provide the effect of significantly reducing the corrosion failure rate of steel materials exposed to harsh external environments such as snow, rain, moisture, and salt for a long period of time and providing unrivaled long-term corrosion resistance.

[0019] According to the present invention, by fundamentally eliminating the cost of discarding parts and unnecessary rework caused by thickness non-uniformity (1 to 40 μm), which was a chronic problem of conventional technology, there is an economic effect of maximizing production yield and drastically reducing manufacturing costs. Specific details for implementing the invention

[0020] Hereinafter, the phosphate coating treatment agent composition according to the present invention will be described in detail.

[0021] The phosphate coating treatment agent composition according to the present invention is characterized by the technical feature of enabling precise control and maintenance of the final coating thickness within the range of 3 to 5 μm.

[0022] The phosphate coating treatment agent composition according to the present invention comprises phosphoric acid, zinc oxide, nitric acid, citric acid monohydrate, calcium carbonate, nickel nitrate, manganese metal, and copper sulfate.

[0023] Phosphoric Acid

[0024] Phosphoric acid performs an etching action on the metal surface to improve adhesion to the metal material to be coated, and stably dissolves metal-based active ingredients such as zinc oxide, calcium carbonate, and metal manganese mixed together, thereby inducing a uniform chemical conversion reaction and allowing the film to grow.

[0025] This phosphoric acid is included in a ratio of 25 to 35 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 30 parts by weight.

[0026] Here, if the phosphoric acid content is less than 25 parts by weight, the etching ability on the metal surface is insufficient, which may reduce the adhesion of the phosphate film or significantly slow down the reaction rate of film formation, making it difficult to form a film of the desired thickness of 3 to 5 μm in time.

[0027] Conversely, if the phosphoric acid content exceeds 35 parts by weight, the metal surface may be damaged due to excessive etching reactions or the thickness of the film may become excessively thick, thereby impairing dimensional stability, and there is a risk that the density of the film may decrease due to increased unnecessary sludge generation caused by strong acidity.

[0028] Zinc Oxide

[0029] Zinc oxide serves as a key source of metal ions that form the main components (such as hoplite crystals) of the phosphate film precipitated on the metal surface, inducing dense crystals and enabling the direct realization of the anti-corrosion and anti-corrosion performance intended by the present invention.

[0030] Such zinc oxide is included in a ratio of 23 to 33 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 28 parts by weight.

[0031] Here, if the zinc oxide content is less than 23 parts by weight, the supply of zinc ions to form a film is insufficient, so the growth of the film structure on the metal surface is not properly carried out, and as a result, the density of the final film decreases, and the anti-corrosion and anti-rust performance in harsh external environments may rapidly deteriorate.

[0032] Conversely, if the zinc oxide content exceeds 33 parts by weight, the reaction rate of film formation becomes excessively fast due to ion supersaturation, and the thickness of the final film may exceed 5㎛, which causes thread assembly defects between fastening parts and hinders precise dimensional control (3 to 5㎛ control).

[0033] Nitric Acid

[0034] Nitric acid acts as a powerful oxidizer and promotes the chemical reaction rate, allowing for flexible control of solubility so that metal ions within the manufactured phosphate coating agent composition do not precipitate and can maintain a stable aqueous solution state.

[0035] This nitric acid is included in a ratio of 18 to 28 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 23 parts by weight.

[0036] Here, if the nitric acid content is less than 18 parts by weight, the reaction rate of the phosphating reaction may decrease, making it impossible to form dense crystals, and the initial film formation reaction may be delayed, which may reduce process efficiency.

[0037] Conversely, if the nitric acid content exceeds 28 parts by weight, a large amount of gas is generated during the film formation process due to excessive oxidation reactions, which can destroy the uniformity of the film and cause serious difficulties in precisely controlling the final film thickness within the range of 3 to 5 μm.

[0038] Citric Acid Monohydrate

[0039] Hydrochloric acid is an organic acid-based chelating agent that suppresses the formation of sludge, which is an unnecessary precipitate generated in the reaction tank during the chemical coating process, and enables long-term storage stability of the phosphate coating treatment agent composition and the phosphate coating treatment agent composition diluted in a solvent.

[0040] This hydrated citric acid is included in a ratio of 2 to 8 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 5 parts by weight.

[0041] Here, if the content of hydrated citric acid is less than 2 parts by weight, the chelating ability is insufficient, so an excessive amount of sludge is generated during the coating reaction, and this sludge can contaminate the metal surface or process line, causing a deterioration in the quality of the coating.

[0042] Conversely, if the content of hydrated citric acid exceeds 8 parts by weight, the film formation reaction itself is inhibited due to excessive complex formation with metal ions, and as a result, a problem may arise in which a chemical conversion film of the desired thickness is not formed normally.

[0043] Calcium Carbonate

[0044] Calcium carbonate acts as a crystal modifier that refines the crystal grains of the film, enabling the precise control of the size of precipitated phosphate crystals to induce a fine and dense film structure.

[0045] Such calcium carbonate is included in a ratio of 2 to 8 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 5 parts by weight.

[0046] Here, if the calcium carbonate content is less than 2 parts by weight, the crystal refinement effect is negligible, so the crystal grains of the phosphate film become coarse, and as a result, the thickness variation increases, which may lead to failure in dimensional control to stabilize the final film thickness within the range of 3 to 5 μm.

[0047] Conversely, if the calcium carbonate content exceeds 8 parts by weight, the pH balance (hydrogen ion concentration equilibrium) within the composition is disrupted, and there is a risk that an uneven coating film may be formed on the metal surface or the initial reaction mechanism may be disturbed.

[0048] Nickel Nitrate

[0049] Nickel nitrate is a reaction accelerator that strongly induces the formation of initial anti-corrosion nucleations on metal surfaces and rapidly precipitates crystals, while simultaneously compensating for defects in the coating to maximize the synergy of anti-corrosion performance.

[0050] To this end, nickel nitrate is included in a ratio of 2 to 8 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 5 parts by weight.

[0051] Here, if the nickel nitrate content is less than 2 parts by weight, the uniformity of the initial film formation reaction decreases, and structural defects such as pinholes may occur within the film layer, which directly leads to a decrease in corrosion resistance.

[0052] Conversely, if the nickel nitrate content exceeds 8 parts by weight, the stress of the formed film layer may increase, which may reduce flexibility, and as a result, adverse effects may occur in which the film easily peels off or detaches during physical assembly and strong torque fastening of construction fastening parts.

[0053] Manganese Metal

[0054] Metallic manganese organically combines with zinc oxide to form a zinc-manganese mixed phosphate film layer, thereby increasing resistance to harsh corrosive environments (snow, rain, moisture, high concentrations of salt, etc.) and enabling the imparting of high corrosion resistance.

[0055] Metallic manganese is included in a ratio of 1 to 6 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 3 parts by weight.

[0056] Here, if the content of metallic manganese is less than 1 part by weight, the film modification effect by manganese ions is insufficient, and it may be difficult to achieve the intended long-term corrosion prevention reliability under harsh corrosion environments (such as salt spray tests).

[0057] Conversely, if the content of metal manganese exceeds 6 parts by weight, the solubility of metal ions in the composition may reach a saturated state, causing uneven crystal precipitation and worsening the roughness of the film surface, which may impair dimensional accuracy.

[0058] Copper Sulfate

[0059] Copper sulfate acts as a trace catalyst to finely control the initial phosphating reaction rate and provides electrochemical active sites that allow zinc and manganese ions to adhere densely and uniformly to the metal surface.

[0060] Copper sulfate is included in a ratio of 0.5 to 3 parts by weight per 100 parts by weight of the phosphate coating agent composition, preferably in a ratio of 1 part by weight.

[0061] Here, if the copper sulfate content is less than 0.5 parts by weight, the catalytic activity is insufficient, and the initial reaction initiation rate may vary locally, which causes non-uniformity (thickness variation) in the final film thickness.

[0062] Conversely, if the copper sulfate content exceeds 3 parts by weight, excessive substitution precipitation of copper components may occur, which may disrupt the electrochemical catalyst balance and, conversely, reduce the long-term corrosion resistance of the film or form unnecessary corrosion cells.

[0063] Meanwhile, the phosphate coating treatment agent composition according to the present invention can be prepared in the form of a concentrated stock solution, and when applied to an actual metal surface, it can be diluted in a solvent to perform a chemical conversion coating reaction in an aqueous solution state.

[0064] The solvent dissolves and ionizes phosphoric acid, zinc oxide, nitric acid, hydrated citric acid, calcium carbonate, nickel nitrate, metallic manganese, and copper sulfate, enabling the maintenance of a homogeneous mixture.

[0065] For example, when using the phosphate coating treatment agent composition according to the present invention, the solvent may be diluted in a ratio of 1 to 9 by weight with respect to 1 by weight of the phosphate coating treatment agent composition (concentrated stock solution).

[0066] Here, if the ratio of solvent to 1 part by weight of phosphate coating agent composition is less than 1 part by weight, the concentration of the phosphate coating agent composition becomes excessively high, causing the reaction rate to become excessively fast, which may result in the coating thickness exceeding 5㎛, cause assembly defects of the screw threads, and cause an increase in the generation of unnecessary sludge.

[0067] Conversely, if the ratio of solvent to 1 part by weight of the phosphate coating agent composition exceeds 9 parts by weight, the concentration of the active ingredient becomes excessively low, resulting in insufficient precipitation of coating crystals on the metal surface or uneven formation of the coating, making it difficult to secure the desired long-term corrosion resistance.

[0068] Therefore, in order to simultaneously satisfy stable thin film thickness variation control and anti-corrosion reliability, it is desirable to use a solvent diluted within the above ratio range of 1 to 9.

[0069] Preferably, the solvent may include one or more of purified water, deionized water (DI water), or distilled water.

[0070] More preferably, the phosphate coating treatment agent composition according to the present invention can be used to perform surface treatment by dipping the metal to be converted into a chemical film in an aqueous solution state or by spraying it onto the surface of the metal.

[0071] <Example: Preparation and Dilution of Phosphate Coating Treatment Agent Composition According to the Present Invention>

[0072] <Example 1>

[0073] A phosphate coating treatment agent composition in the form of a concentrated stock solution of 100 parts by weight was prepared by uniformly mixing 30 parts by weight of phosphoric acid, 28 parts by weight of zinc oxide, 23 parts by weight of nitric acid, 5 parts by weight of hydrated citric acid, 5 parts by weight of calcium carbonate, 5 parts by weight of nickel nitrate, 3 parts by weight of metallic manganese, and 1 part by weight of copper sulfate.

[0074] Subsequently, in order to perform actual metal surface treatment, 400 parts by weight of deionized water (DI Water), which is a solvent, was added and mixed with 100 parts by weight of the phosphate coating agent composition in the form of a concentrated stock solution to complete the final diluted aqueous solution for surface treatment.

[0075] <Comparative Example 1>

[0076] We prepared a general commercial phosphate coating agent currently available on the market.

[0077] <Experimental Example: Evaluation of Film Performance and Dimensional Stability>

[0078] After performing a chemical conversion coating surface treatment process by immersing each of 30 high-strength construction bolts (M24 size) in the diluted aqueous solution of Example 1 and the commercial coating agent of Comparative Example 1, which were maintained at a temperature of 60°C for 5 minutes, the thickness variation and long-term corrosion resistance of the finally formed coating were evaluated.

[0079] <Evaluation of Coating Thickness Uniformity (Dimensional Control) and Axial Force / K Value Stability>

[0080] The film thickness was measured using a micrometer on each of the 30 bolt threads surface-treated according to Example 1 and Comparative Example 1, the maximum / minimum deviation was confirmed, and the thread assembly defect rate was evaluated.

[0081] In addition, to evaluate the stability of the clamping force and torque coefficient (K value, Torque Coefficient), which are key quality indicators of high-strength bolts for construction, clamping tests were performed on surface-treated bolts, and the results are shown together in [Table 1] below.

[0082] division Minimum film thickness (㎛) Maximum film thickness (㎛) Screw thread assembly defects (%) Example 1 3.2 4.8 0% Comparative Example 1 1.0 40.0 16.7%

[0083] As can be seen in [Table 1] above, in the case of Comparative Example 1 using a general commercial coating agent, extreme thickness variation ranging from a minimum of 1 μm to a maximum of 40 μm was observed, making precise dimensional control of the screw threads impossible. Consequently, not only were numerous assembly defects occurring, but the non-uniformity of the coating also caused significant dispersion in the axial force and K values ​​during fastening, resulting in failure to meet construction standards.

[0084] On the other hand, in the case of Example 1 according to the present invention, the final film thickness was precisely controlled within a target range of 3 to 5 μm, maximizing thickness uniformity, and dimensional stability was proven by achieving a screw thread assembly defect rate of 0%.

[0085] On the other hand, in the case of Example 1 according to the present invention, the final film thickness was precisely controlled within a target range of 3 to 5 μm, maximizing thickness uniformity and achieving a screw thread assembly defect rate of 0%.

[0086] In particular, for high-strength bolts used in construction, the stabilization of axial force and K values ​​serves as the most important performance factor to ensure not only the assembly of the parts but also the structural stability of the structure after fastening. Our test results confirmed a critical effect in which the friction characteristics between screw threads are most uniformly controlled and the axial force and K values ​​are extremely stabilized when the coating thickness physically forms an ultra-precision thin film range of 3 to 5 μm.

[0087] Accordingly, it has been proven that the phosphate coating treatment composition according to the present invention possesses technical advantages suitable for the field of high-strength construction bolts and nuts, where dimensional stability and fastening reliability are simultaneously required in harsh environments.

[0088] <Evaluation of Long-term Corrosion Resistance (Salt Spray Test)>

[0089] In order to precisely evaluate the inherent anti-corrosion performance of the phosphate coating on construction parts surface-treated according to Example 1 and Comparative Example 1, a 5% concentration of NaCl brine solution was continuously sprayed in a 35°C environment in accordance with ASTM B117 standards in a 'rust-free state' in which the subsequent anti-corrosion oil application treatment was not performed. Subsequently, the time until the first red rust (rust) appeared on the surface of the parts was measured and is shown in [Table 2] below.

[0090] division Time (hr) for final reddish-blue (green) discoloration to occur Corrosion resistance in harsh environments Example 1 No occurrences for more than 3 hours Excellent (meets construction standards) Comparative Example 1 Occurs within 2 hours Defective (weak corrosion resistance)

[0091] As shown in the results of [Table 2] above, although Example 1 of the present invention forms a very thin film of 3 to 5 μm, it forms a closed film with an extremely dense structure due to the interaction of phosphoric acid, zinc oxide, nitric acid, citric acid monohydrate, calcium carbonate, nickel nitrate, manganese metal, and copper sulfate. It was confirmed that the initial corrosion resistance and long-term corrosion prevention reliability were significantly improved compared to Comparative Example 1, even under the 'no corrosion prevention condition' itself, regardless of whether corrosion prevention is performed in the subsequent process.

[0092] In particular, since the phosphate coating process is generally linked to the application of anti-rust oil as a subsequent process, the corrosion resistance of the final product may vary depending on the specifications of the anti-rust oil applied. However, the composition according to the present invention forms an ultra-high-density coating that does not cause red rust within approximately 3.5 hours even in a rust-free state. Therefore, it offers technical advantages that maximize applicability and phase synthesis with various anti-rust specifications (such as types of anti-rust oil) in the future, enabling smooth response to various subsequent process environments. Accordingly, it has been confirmed that it is optimized for fastening components for large building structures exposed to harsh external environments.

[0093] Although specific embodiments of the present invention have been described above, it is obvious to those skilled in the art that the present invention is not limited to the described embodiments and can be modified and varied in various ways without departing from the spirit and scope of the invention. Accordingly, such modifications or variations should not be understood individually from the technical spirit or perspective of the present invention, and the modified embodiments should be considered to fall within the scope of the claims of the present invention.

Claims

Claim 1 A phosphate coating treatment agent composition comprising, for every 100 parts by weight of the phosphate coating treatment agent composition, 25 to 35 parts by weight of phosphoric acid, 23 to 33 parts by weight of zinc oxide, 18 to 28 parts by weight of nitric acid, 2 to 8 parts by weight of hydrated citric acid, 2 to 8 parts by weight of calcium carbonate, 2 to 8 parts by weight of nickel nitrate, 1 to 6 parts by weight of metallic manganese, and 0.5 to 3 parts by weight of copper sulfate, wherein, when used, the phosphate coating treatment agent composition is diluted in a solvent comprising one or more of purified water, deionized water (DI water), or distilled water to form a phosphate coating on a metal surface, wherein 1 part by weight of the phosphate coating treatment agent composition is diluted in 1 to 9 parts by weight of the solvent. Claim 2 A phosphate coating treatment agent composition according to claim 1, characterized in that the phosphate coating is formed with a thickness of 3 to 5 μm. Claim 3 delete Claim 4 delete Claim 5 A phosphate coating treatment agent composition according to claim 1, characterized by comprising in the ratio of 30 parts by weight of phosphoric acid, 28 parts by weight of zinc oxide, 23 parts by weight of nitric acid, 5 parts by weight of hydrated citric acid, 5 parts by weight of calcium carbonate, 5 parts by weight of nickel nitrate, 3 parts by weight of metallic manganese, and 1 part by weight of copper sulfate.

Citation Information

Patent Citations

  • Zinc phosphate surface treatment composite

    KR101359967B1

  • Zinc-calcium based coloring composition, preparationthereofand parkerizing process using the same

    KR1020020089214A

  • A conversion coating composition providing a thickfilm in middle temperature

    KR1020060019272A